Reducing Defects in Denim Weaving by Applying Six Sigma Methodology: A Case Study (Global Journal of Human-Social Science, 2019)
Denim is one of the most key portions of the Bangladeshi textile sector. The worldwide consumption of denim by fashion experts has created a new opportunity for Bangladesh. Bangladeshi entrepreneurs supply denim products to major global retailers across the world. It estimates that till 2020 the global denim market will grow by about 8%. To keep up with the growing trade, we need to improve the quality of the denim. The head objective of this study is to apply the six-sigma methodologies for reducing defects in denim fabric manufacturing companies. Define, Measure, Analyze, Improve and Control also known as DMAIC method is used here. This study covers a denim weaving mill, and it finds that by proper application of six sigma tool the sigma level could be improved from 3.1 to 3.5 increasing the company's profit with customer satisfaction.
Keywords: denim; weaving unit; six-sigma; DMAIC method; quality